-7(2t+8)=-126

Simple and best practice solution for -7(2t+8)=-126 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(2t+8)=-126 equation:


Simplifying
-7(2t + 8) = -126

Reorder the terms:
-7(8 + 2t) = -126
(8 * -7 + 2t * -7) = -126
(-56 + -14t) = -126

Solving
-56 + -14t = -126

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '56' to each side of the equation.
-56 + 56 + -14t = -126 + 56

Combine like terms: -56 + 56 = 0
0 + -14t = -126 + 56
-14t = -126 + 56

Combine like terms: -126 + 56 = -70
-14t = -70

Divide each side by '-14'.
t = 5

Simplifying
t = 5

See similar equations:

| r+(-016)=0.37 | | 5(f-1)=-25 | | (7a^3-2a^2-4a+9)+(3a+6)-(-a^2-a+3)= | | 14x+18y=63 | | -9(T-2)-(t+3)=2 | | x+44=4x+17 | | 2(3x+4)=2x+1 | | 8(s-7)=-92 | | 3x-4=x-10 | | 3x+4+x+20=180 | | 8x+6y=120 | | S^2-s-12=0 | | 8(2l+2)=32 | | 4x+(-7x)=9 | | 3(a-5)=54 | | -3x+7+2x=5 | | 8x-4+12+6x=180 | | 50x^2+40x-45=0 | | 48-92+67=y | | 25x-4x+y=36 | | (2x-5)(3x^2+3x-1)= | | p-4/11=29/11 | | (x+8)-x-(5-6)=15 | | X^3-5x-14x=0 | | 5c-(-32)=87 | | 4-6x=3y | | 3w^2-12w+16=0 | | 9-3x+5=2x+4 | | 10+5=515 | | 4n+2=7n-13 | | 24-3c=3 | | x^2-27x+1=0 |

Equations solver categories